Having Social Media among Integrated Plastic Surgery Applicants: Is It Needed to Match? - Alan Z. Yang, MSc; Valeria P. Bustos, MD, MSc; Samuel M. Manstein, MD; Carly D. Comer, MD; Lacey Foster, MS; Benjamin A. Sarac, MD; Jeffrey E. Janis, MD; Samuel J. Lin, MD, MBA (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Little information exists on the perceptions of integrated plastic and reconstructive surgery (PRS) residency applicants on the need for having social media (SoMe) during the application process. Methods:. A cross-sectional survey study was conducted during the 2022 match cycle to assess integrated PRS residency applicants’ perceptions on the role of SoMe during the match. Univariate and multivariate analyses were performed on variables of interest. Qualitative analysis was conducted on free-form responses. Results:. Seventy-nine surveys were completed (response rate: 24%). The majority of respondents were educated in the United States (92%). Instagram was the most commonly used SoMe platform (92%). Of those surveyed, 18% thought that SoMe was beneficial to the application process. Twenty-nine percent of respondents agreed that a SoMe presence increases one’s chances of matching into PRS residency (41% disagreed and 30% responded neutrally). Forty-four percent endorsed stress about maintaining a SoMe presence in PRS. Having mentors who recommended maintaining a SoMe presence was associated with the belief that SoMe increases one’s chances of matching [odds ratio (OR) 8.1, 95% confidence interval (CI) 1.1–40.4, P = 0.011] and stress about maintaining a SoMe presence (OR 6.3, 95% CI 1.2–33.3, P = 0.030). Applicants who did research years had lower odds of experiencing stress (OR 0.16, 95% CI 0.04–0.70, P = 0.015). Conclusions:. The growing role of SoMe in the residency selection process may be exacerbating applicants’ stress and anxiety. PRS programs may consider establishing clear policies for how SoMe will be used in evaluating candidates.